2021
DOI: 10.1016/j.biopsych.2021.02.561
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cannabis Withdrawal Symptoms Among People With Regular or Dependent Use of Cannabinoids: A Systematic Review and Meta-Analysis

Abstract: IMPORTANCE Cannabis withdrawal syndrome (CWS)-a diagnostic indicator of cannabis use disorder-commonly occurs on cessation of heavy and prolonged cannabis use. To date, the prevalence of CWS syndrome has not been well described, nor have the factors potentially associated with CWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
(106 reference statements)
0
13
0
Order By: Relevance
“…We followed analytic approaches of previous NMAs for trials of treatments for psychiatric disorders, [40][41][42][43][44][45][46] employing the netmeta package from R Studio (version 3.5.1) software. 47,48 We graphed forest plots for each outcome measure (retention in treatment, dropouts, dropouts for adverse events, and total psychotic symptom rating score).…”
Section: Planned Methods Of Analysismentioning
confidence: 99%
“…We followed analytic approaches of previous NMAs for trials of treatments for psychiatric disorders, [40][41][42][43][44][45][46] employing the netmeta package from R Studio (version 3.5.1) software. 47,48 We graphed forest plots for each outcome measure (retention in treatment, dropouts, dropouts for adverse events, and total psychotic symptom rating score).…”
Section: Planned Methods Of Analysismentioning
confidence: 99%
“…Cessation from long-term cannabinoid use often precipitates a specific set of symptoms known as cannabis withdrawal syndrome, and sleep disturbances are one of six diagnostic criteria for this condition (Bonnet and Preuss, 2017). A meta-analysis found that 47% of regular cannabis users exhibited cannabis withdrawal syndrome following discontinuation of use (Bahji et al , 2020). A systematic review of cannabis withdrawal and sleep notes that, while sleep disruption following withdrawal appears to be common across multiple studies, small sample sizes and the presence of confounding variables limit determination of the specific aspects of sleep that are affected (Gates et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interrupted use of cannabis, the most commonly used illicit drug, likewise has been associated with withdrawal symptoms. By some estimates up to 30–70% of daily users, and 10–17% of all users, describe symptoms associated with spontaneous cannabis withdrawal (Copersino et al , 2006; Agrawal et al , 2008; Bahji et al , 2020). However, like nicotine or caffeine dependence, the predominant symptoms of cannabinoid abstinence such as nightmares, angry outbursts, and difficulty falling asleep are psychometric and, consequently, difficult to translate to animal models (Allsop et al , 2011).…”
Section: Introductionmentioning
confidence: 99%